IMeta: Integrated meta‐omics for biology and environments. Issue 1 (28th March 2022) - Liu, Yong‐Xin; Chen, Tong; Li, Danyi; Fu, Jingyuan; Liu, Shuang‐Jiang
Abstract : The cover of iMeta's inaugural issue. The galaxy represents the complexity and value of bioinformatics and metagenomics. DNA, which represents genetic components that guide biological diversity, is at the center of the galaxy. The spiral arms are the microbiome welcoming scientists from all over the world to make novel discoveries. Let us usher in the metaverse era of the microbiome.